Drug Utilization Study of Corticosteroid Sparing Agent In Pediatric Patient With Lupus Nephritis (Study at Pediatric Department of Dr. Soetomo Teaching Hospital, Surabaya) - Chatarina Widianti; Yulistiani Yulistiani; Ninik Asmaningsih Soemyarso (Syntax Corporation, 2022)
Lupus nephritis occurs mostly in children. The main therapy used is long-term corticosteroids that can lead to organ damage, which should be treated by providing corticosteroid sparing agent; to control the underlying disease and reduce the side effects of corticosteroid therapy and facilitate tapering off. This study analyzed the drug utilization profile and the tapering off pattern of corticosteroid and corticosteroid sparing agents and identified potential adverse effects of corticosteroid sparing agents in pediatric patients with LN. The study used observational method that was analyzed descriptively on 37 patients with hospitalization period of January 2016 until December 2017. The profile of corticosteroid sparing agent in patients with LN was a combination of oral MMF and oral chloroquine. Oral cyclosporine A was added if persistent proteinuria> 1 g / day / 1.73 m2 after three months of therapy and combination of IV CPA pulse and oral chloroquine. The tapering off pattern of oral prednisone in the presence of corticosteroid sparing agent was in accordance with the Clinical Practice Guide, which was decrease of 5 mg/day every month. Actual adverse effects included leucopenia (34%), hepatotoxicity (13%), GIT disorders (45%), and several potential adverse effects. The utilization of corticosteroid sparing agent in pediatric patients with LN in Dr. Soetomo Hospital was in accordance with Clinical Practice Guide (PPK) issued by Dr. Soetomo General Hospital. Both regular monitoring of patients as well as enhanced interprofessional collaboration are required to monitor adverse effects of corticosteroid sparing agents.